General Training by Firms, Apprentice Contracts, and Public Policy. - Malcomson, J; Maw, J; McCormick, B (Department of Economics (University of Southampton), 2000)
Workers will not pay for general on-the-job training if contracts are not enforceable. Firms may if there are mobility frictions. Private information about worker productivities, however, prevents workers who quit receiving their marginal products elsewhere. Their new employers then receive external benefits from their training. Training firms increase profits by offering apprenticeships committing them to high wages for trainees retained on completion. At those wages, only good workers are retained, which signals their productivity and reduces the external benefits if they subsequently quit. Regulation of apprenticeship length (a historically important feature) can enhance efficiency, as can appropriate subsidies.